Effects of exerimental right ventricular hypertrophy on myocardial blood flow in conscious dogs. - Murray, P A (1979)
The effects of right ventricular hypertrophy on the overall and regional distribution of myocardial blood flow in the absence of an elevated coronary arterial driving pressure were evaluated in 18 concscious dogs subjected to a chronic pressure overload of the right ventricle induced by pulmonary artery constriction. The sustained pressure overload for duration of 4--6 wk or 4--5 mo resulted in significant increases in right ventricular mass (45 and 110%, respectively) and right ventricular fiber diameter (22 and 60%, respectively). Moreover, the presence of moderate and severe hypertrophy was associated with marked increases in transmural blood flow per gram to the right ventricle proportional to the observed increases in mass, i.e., of 36 and 109%, respectively, from a normal value of 0.67 +/- 0.04 ml/min per g, whereas left ventricular blood flow remained unaltered from a normal value of 1.00 +/- 0.06 ml/min per g. Despite the large increase in blood flow per gram to moderately and severely hypertrophied right ventricle, no significant changes in the ratio of capillary:muscle fiber number were observe. These data suggest that the development of right ventricular hypertroph is characterized by a sustained compensatory response of the coronary circulation to the augmented work load and mass, and that is not associated with a proliferative response of the vasculature supplying the enlarged ventricle.